An M/G/1 Retrial Queueing System with Phase Type Services and Working Vacations - Rajadurai, P.; Santhoshi, R.; Pavithra, G.; Usharani, S.; B. Shylaja, S. (International Journal of Engineering and Technology, 2018)
A multi phase retrial queue with optional re-service and multiple working vacations is considered. The Probability Generating Function (PGF) of number of customers in the system is obtained by supplementary variable technique. Various system performance measures are discussed.Â